Porcine LEM domain-containing 3: Molecular cloning, functional characterization, and polymorphism associated with ear size - Jing LIANG; Na LI; Long-chao ZHANG; Li-gang WANG; Xin LIU; Ke-bin ZHAO; Hua YAN; Lei PU; Yue-bo ZHANG; Hui-bi SHI; Qin ZHANG; Li-xian WANG (Journal of Integrative Agriculture, 2016)
Ear size exhibits remarkable diversity in pig breeds. LEM domain-containing 3 (LEMD3) on chromosome 5 is considered as an important candidate for porcine ear size. This is the first study on cloning and characterization of LEMD3 cDNA. The complete cDNA contains 4 843 bp, including a 2 736-bp open reading frame (ORF), a 37-bp 5′-untranslated region (UTR) and a 2 070-bp 3′-UTR. The complete LEMD3 gene is 126 241-bp and contains 13 exons and 12 introns. The ORF encodes a deduced LEMD3 protein of 911 amino acids, which shares 82–94% nucleic acid and 51–96% amino acid identity with other species. A phylogenetic tree constructed based on the amino acid sequences revealed that the porcine LEMD3 protein was closely related with cattle LEMD3. Resequencing of the ORF and promoter of LEMD3 from Minzhu pig and Large White revealed three single nucleotide polymorphisms (SNPs): L964C>A in the complete coding region, L4625A>G in the 3’ UTR, and L-394T>C in the promoter region. Genome-wide association study (GWAS) revealed that all of SNPs were shown significant association with ear size in Large White×Minzhu pig intercross population. With conditional GWAS, –log10(P-value) decreased by more than 80% when each of three SNPs was included as a fixed effect. These results suggested direct involvement of LEMD3 or close linkage to the causative mutation for ear size. The findings of this study might form the basis for understanding the genetic mechanism of ear size variation in pigs and provide potential molecular markers for screening ear size diversity in pig breeds.